HUKUMAN DISIPLIN TERHADAP ASN YANG MELAKUKAN PENCALOAN CPNS MENURUT UNDANG-UNDANG NO.5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA (PUTUSAN NOMOR 4/G/2023/PT.TUN.JKT): Disciplinary Punishment on Civil Servants (ASN) Involved in CPNS Brokerage According to Law No. 5 of 2014 on State Civil Apparatus (A Decision Number 4/G/2023/PT.TUN.JKT) - Irvandi Putra; Reni Dwi Purnomowati (AMICUS CURIAE, 2025)
Disciplinary Punishment for ASN Nomination for CPNS according to Law No. 5 of 2014 concerning the State Civil Apparatus. The identification of the problem in this article is whether the imposition of penalties on ASN who nominate for CPNS within the Ministry of Law and Human Rights is in accordance with Law Number 5 of 2014 concerning the State Civil Apparatus and what are the legal consequences of decision number 4/G/2023/PT. TUN. JKT on the ASN staffing. The type of research used is normative legal research based on descriptive secondary data and analyzed qualitatively with deductive conclusions. The results of the research and conclusion in this case, what happened to the plaintiff, namely LYZA ZASTAVARY, sued the chairman of BPASN and the Minister of Law and Human Rights for the imposition of disciplinary punishment in the form of disrespectful dismissal. In this case, the plaintiff is considered to have violated the obligations and prohibitions of civil servants by committing fraud, fraud, and embezzlement in the receipt of CPNS. Because he felt unfair, plaintiff filed a lawsuit on the grounds that the weight of the punishment was not proportional to the weight of the error in application of the phrase "brokerage".